Physicochemical Properties and Sensory Evaluation of ‘Keropok Lekor Banana Heart’ - MOHD NAZAR, NUR AFIQAH; Nazar, Afiqah (Enhanced Knowledge in Sciences and Technology, 2024)
The Keropok Lekor Banana Heart is a new snack product designed to promote its nutritional value. The product's physicochemical properties were thoroughly examined, providing insights into its composition and potential health benefits. The formulation was optimized using the simplex lattice mixture design method, facilitated by Design Expert software. This innovative approach not only introduces a unique product to the market but also addresses the dietary needs of individuals allergic to fish, a common ingredient in traditional keropok lekor. Formulation 13 (grated coconut, oyster mushroom, potato) has the highest moisture level ever measured, with an impressive 48.41% moisture content. Formulation 13 (30.61±1.05) has a much higher lightness than the other formulations when it comes to L* values, which measure the lightness of keropok lekor. The pH range of 5.9 to 7.2 is present in all keropok lekor banana heart compositions. Formulation 1 records the maximum performance work of shear value and firmness for physicochemical parameters. The sensory evaluation revealed that all 13 variations of the Keropok Lekor Banana Heart were well-accepted by panelists. The nutritional analysis highlighted the richness of vital vitamins, minerals, and dietary fiber in the new formulation, positioning it as a healthful complement to a balanced diet.